Physical Activity on Erectile Dysfunction: Screening and Counseling in Kendalkerep Community Health Center Area - Yhusi Karina Riskawati; Kurnia Penta Seputra; Paksi Satyagraha; Reza Amorga (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2026)
Introduction. Erectile dysfunction negatively impacts self-esteem, quality of life, and interpersonal relationships. Studies have shown significant improvements in sexual function in men and women who undergo regular moderate-intensity physical exercise interventions. However, public awareness of the importance of physical activity in sexual health remains low. This study aims to evaluate the relationship between physical activity level and erectile function among community members in the Kendalkerep Primary Health Care area. Methods. This is an observational analytic study with a cross-sectional design involving 50 adult men who participated in screening and educational activities, selected using incidental sampling. Physical activity levels were categorized as low, moderate, and high, while erectile function was assessed using the International Index of Erectile Function-5 (IIEF-5). Descriptive and bivariate analyses were performed using Spearman correlation tests. Result. The results demonstrated a strong positive correlation between physical activity level and IIEF-5 score (ρ = 0.702; p < 0.001), as well as a significant negative correlation between physical activity level and erectile dysfunction severity (ρ = −0.643; p < 0.001). Body mass index and blood pressure were also significantly associated with erectile function, whereas age showed no significant correlation. Conclusion. Higher levels of physical activity are associated with better erectile function. Physical activity may serve as an effective non-pharmacological strategy for the prevention of erectile dysfunction at the community level.